Ratifying the HCCH 2005 and 2019 Conventions: Legal Reform and the Pursuit of Certainty in Indonesia’s International Private Law - Antony, Antony; Osmond, Agung Pratama; Sabisi, Muhammad Ali; Shahrullah, Rina Shahriyani (Institute for Law and Economics Studies, 2025)
In the era of globalization, the increasing intensity of cross-border transactions demands a national legal system capable of ensuring legal certainty in international trade. However, Indonesia has yet to ratify the HCCH 2005 Convention on Choice of Court Agreements and the HCCH 2019 Convention on the Recognition and Enforcement of Foreign Judgments. This study aims to analyze the urgency of ratifying both conventions in the context of Indonesia’s international trade, assess the readiness of national legal and institutional frameworks, and examine lessons learned from countries that have ratified similar conventions. This research adopts a normative legal approach using three methods: the statutory approach to examine the relevance of national regulations, the conceptual approach to understand the foundational principles of the HCCH conventions, and the comparative approach through case studies of ratifying countries. The data sources consist of primary legal materials such as international conventions and national legislation, as well as secondary materials including scholarly journals and legal literature. The research question in this study is: 1) What is the urgency of ratifying the 2005 and 2019 HCCH Conventions in Indonesia?; 2) How prepared is Indonesia's legal and institutional system to accept the ratification of the 2005 and 2019 HCCH Conventions?; and 3) What lessons can Indonesia learn from countries that have ratified the 2005 and 2019 HCCH Conventions?. The findings reveal that, despite Indonesia's significant economic potential, its legal system has not yet adequately accommodated the recognition of jurisdiction and enforcement of foreign judgments. Countries such as Mexico, Singapore, and members of the European Union have demonstrated that ratifying these conventions strengthens legal certainty, enhances investor confidence, and expedites the resolution of cross-border disputes. This study concludes that the ratification of the HCCH 2005 and 2019 Conventions must be an integral part of Indonesia’s civil law reform agenda. The implication is that Indonesia must revise its national regulations, enhance institutional capacity, and develop a structured ratification roadmap to ensure effective implementation and reinforce its legal standing within the global system